PROBLEMS OF GEOLOGICAL INTERPRETATION OF SEISMIC-FOCI SYSTEMS OF THE EARTH’S CRUST (GEOMECHANICS AND TECTONOPHYSICAL ANALYSIS) - Boris M. Chikov (Геодинамика и тектонофизика, 2015)
In our study, an earthquake focus is viewed as a 3D zone of the Earth’s crust, wherein the discharge of mechanical loading is accompanied by recordable destruction and qualitative transformation of the geological medium. The purpose of the present publication is to make an attempt to reveal a direct relationship between seismicity and deformation-metamorphic processes which took place in the Earth’s crust. Traditional and alternative interpretations of geomechanics of seismic-foci situations are discussed. The problems of geodynamics and geostatics of the seismic-foci systems and their concentrations, as well as anthropogenic models and mechanisms of focus medium structuring are reviewed. The relationship between seismicity and mechanisms of «regional shearing» or formation of crustal deformation-metamorphic structures of lineament type is outlined in the example of the Chuya seismic system of earthquakes which occurred in 2003 and afterwards in the Altai region.